DEVELOPMENT OF FORMAN MORAL DEVELOPMENT SCALE FOR YOUNG ADULTS - Muzammil, Maheen; Majeed, Saima (Journal of Pakistan Psychiatric Society, 2024)
ABSTRACT Objectives: To identify the moral components especially in Pakistani cultural context and to develop an indigenous scale of Moral Development for young adultsPlace and Duration of Study: Lahore, Pakistan. 1 year.Design and Method: The study was carried out into 2 phases; in the first phase, a pool of 40 items was generated while conducting two separate focus groups with clinical psychologists and young adults and , and semi-structured in-depth interviews with university professors. A 5-point Likert scale of 40 items was developed. 280 young adults, aged 18-25, (M=139(49.6%) F=141(50.4%) from two private and government university students were approached through non probability purposive sampling. In the second phase, the scale was administered on young adults, content and construct validity was established. Exploratory factor analysis was conducted using SPSS 25.Results: Principal Component Analysis with Varimax rotation and Kaisar normalization, Kaisar-Meyer-Olkin (KMO) measure of Sample adequacy yielded a value of 0.753, indicating satisfactory sample adequacy, and Bartlett's test of Sphericity was significant (p < 0.001). The Scree plot suggested 4 factors; Moral disengagement, Moral maturity, parental/societal influence, social media/peer influence.  Conclusion: Present study contributed in the development of indigenous assessment tool for young adults of Pakistan. Presently no such tool was available to study moral development in young adults.Key words: Morality, Moral Development, Parental influence, Moral Judgment, Moral maturity, Ethical Sensitivity, Moral disengagement.